ANALYSIS OF e-HRM MODEL AND PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE ENGAGEMENT: A STUDY OF ONLINE TRANSPORTATION DRIVERS IN INDONESIA - Agustini, I Gusti Ayu Ari; Hadikusumo, Reina A.; Yuliana, Yuliana; Udodiugwu, Michael Ikenna (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2025)
In the era of human resource digitalization, e-HRM has become an important tool in supporting team member engagement, including in the informal and application-based sectors such as online transportation. Perceived organizational support is crucial in building psychological bonds between the company and the driver. At the same time, emotional intelligence is believed to help drivers manage work pressure and increase emotional and cognitive engagement. This study aims to analyze the effect of the electronic human resource management (e-HRM) model, perceived organizational support, and emotional intelligence on employee engagement in online transportation drivers in Indonesia. This study uses a quantitative approach with a survey method on a number of online transportation drivers from various platforms in Indonesia. Data analysis was carried out using the regression test model, hypothesis test, correlation test, and coefficient of determination to test the relationship between variables. The results of the study show that the three independent variables, namely e-HRM, perceived organizational support, and emotional intelligence have a significant positive effect on employee engagement. These findings provide practical implications for online transportation service providers in designing more inclusive and technology-based human resource management strategies to increase driver engagement and loyalty.